2013
DOI: 10.1590/1516-3180.2013.1314494
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral tibial hemimelia type 1 (1a and 1b) with T9 and T10 hemivertebrae: a novel association

Abstract: CONTEXT: Congenital absence of the tibia is a rare anomaly with an incidence of one per 1,000,000 live births. It is mostly sporadic and can be identified as an isolated disorder or as part of malformation syndromes. CASE REPORT: A male child, born to unaffected and non-consanguineous parents, presented with shortening of the legs and adduction of both feet. Physical examination at six months of age showed head circumference of 44.5 cm (75 th percentile), length 60 cm (< 3 rd percentile), weight 7,700 g (50 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Some studies showed a tibial hemimelia syndrome in cattle (Apointe et al, 2000). In humans, tibial hemimelia may occur in isolation or may be associated with a variety of skeletal or extra-skeletal malformations, such us polydactyly (Salinas-Torres et al, 2015), as observed in the present case. There are reports of unilateral and / or bilateral tibial hemimelia in cattle (Lapointe et al, 2000).…”
Section: Discussionsupporting
confidence: 50%
“…Some studies showed a tibial hemimelia syndrome in cattle (Apointe et al, 2000). In humans, tibial hemimelia may occur in isolation or may be associated with a variety of skeletal or extra-skeletal malformations, such us polydactyly (Salinas-Torres et al, 2015), as observed in the present case. There are reports of unilateral and / or bilateral tibial hemimelia in cattle (Lapointe et al, 2000).…”
Section: Discussionsupporting
confidence: 50%
“…Tibial hemimelia is a challenging congenital anomaly that is associated with a wide spectrum of other congenital defects and duplications 1,8-11,16-21 . The condition is marked by shortening and bowing of the leg 7,18,21,29,30 . To date, the reconstructive options have been limited, and the most accepted treatment has been amputation followed by a suitable prosthetic replacement 1-5,7-9,17,21,22,27,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The fibula is always present 8 . The incidence of tibial hemimelia has been reported to be 1 per million live births 5,17,18 . Parent-to-child transmission as well as families with multiple affected siblings have been reported 9,13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Foot deformities include clubfeet, syndactyly, missing or duplicated toes, diplopodia, ectrodactyly, micromelia, and a mirror foot deformity [35][36][37][38][39][40][41][42][43]. Other associated deformities include coxa valga, hip dysplasia or dislocation, radial dysplasia, lobster claw deformity, hand syndactyly and polydactyly, triphalagism, mirror hand, missing fingers or toes, hemivertebrae, and myelomeningocele [44][45][46][47]. In addition, cleft palate, deafness, cryptorchidism, pseudo-hermaphroditism, and hypospadias have also been associated with tibial hemimelia [14].…”
Section: Associationsmentioning
confidence: 99%